1995
DOI: 10.1007/bf01700663
|View full text |Cite
|
Sign up to set email alerts
|

Alternating versus synchronous ventilation of left and right lungs in piglets

Abstract: Objective." We tested whether alternating ventilation (AV) of each lung (i. e. with a phase difference of half a ventilatory cycle) would decrease central venous pressure and so increase cardiac output when compared with simultaneous ventilation (SV) of both lungs.Theory: If, during AV, the inflated lung expands partly via compression of the opposite lung, mean lung volume will be smaller during AV than SV. As a consequence, mean intrathoracic pressure (as cited in the literature), and therefore, central venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 17 publications
3
10
1
Order By: Relevance
“…In our two previous studies we found a ratio between right and left V T at a ventilatory rate of 10pbm of 1.30+0.11 [5] and 1.21+0.07 [6], which together give a value of 1.25+0.10, which is equal to the value in the present study of 1.24_+0.10. In our previous paper we regarded the ratio between the two lung volumes as the same as the ratio between both tidal volumes.…”
Section: Tidal Volume To Each Lungsupporting
confidence: 67%
See 4 more Smart Citations
“…In our two previous studies we found a ratio between right and left V T at a ventilatory rate of 10pbm of 1.30+0.11 [5] and 1.21+0.07 [6], which together give a value of 1.25+0.10, which is equal to the value in the present study of 1.24_+0.10. In our previous paper we regarded the ratio between the two lung volumes as the same as the ratio between both tidal volumes.…”
Section: Tidal Volume To Each Lungsupporting
confidence: 67%
“…The details of the surgery have been described previously [5,6]. Twenty young female pigs of 11.0 + 1.0 kg (mean_+ sd) body weight (BW) were anaesthetized with an intraperitoneal injection of 30 mg pentobarbital sodium (Abbott/Sanofi, Maassluis, The Netherlands) per kg BW.…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations